Salinity influences glutathione S-transferase activity and lipid peroxidation responses in the Crassostrea gigas oyster exposed to diesel oil - Zanette, Juliano; de Almeida, Eduardo Alves [UNESP]; da Silva, Angela Zaccaron; Guzenski, Joao; Ferreira, Jaime Fernando; Di Mascio, Paolo; Freire Marques, Maria Risoleta; Dias Bainy, Afonso Celso (Elsevier B.V., 2011)
Biochemical responses in bivalve mollusks are commonly employed in environmental studies as biomarkers of aquatic contamination. The present study evaluated the possible influence of salinity (35, 25,15 and 9 ppt) in the biomarker responses of Crassostrea gigas oysters exposed to diesel at different nominal concentrations (0.01, 0.1 and 1 mLL(-1)) using a semi-static exposure system. Salinity alone did not resulted in major changes in the gill's catalase activity (CAT), glutathione S-transferase activity (GST) and lipid peroxidation levels (measured as malondialdehyde. MDA), but influenced diesel related responses. At 25 ppt salinity, but not at the other salinity levels, oysters exposed to diesel showed a strikingly positive concentration-dependent GST response. At 25 ppt and 1 mLL(-1) diesel, the GST activity in the gills remained elevated, even after one week of depuration in clean water. The increased MDA levels in the oysters exposed to diesel comparing to control groups at 9, 15 and 35 ppt salinities suggest the occurrence of lipid peroxidation in those salinities, but not at 25 ppt salinity. The MDA quickly returned to basal levels after 24 h of depuration. CAT activity was unaltered by the treatments employed. High toxicity for 1 mLL(-1) diesel was observed only at 35 ppt salinity, but not in the other salinities. Results from this study strongly suggest that salinity influences the diesel related biomarker responses and toxicity in C. gigas, and that some of those responses remain altered even after depuration. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Salinity; Diesel; Biomarkers; Pollution; Oxidative stress; Crassostrea gigas